Experts et expertise dans les mandats de la société des nations : figures, champs, outils - Bourmaud, Philippe; Neveu, Norig; Verdeil, Chantal (TransAireS, 2020)
Expertise in the colonial world can be characterized, more perhaps than in any other context, by the tension between abstract knowledge and acquaintance with the field as inspirations for decision making. The League of Nations mandates instituted after World War I should not be understood as a laboratory of expertise in the colonial world, but as an early instance of the implications of bringing experts to the global South. Not only does colonial expertise combine the distance of the expert to their objects and the overbearing position inherent to the colonizer's gaze: the international organizations of the League of Nations system created further institution distance to colonial realities. Yet is the point of involving expertise in the administration of the mandates not to counter the discredited image of brutal colonial, counter-insurrectional rule, by inserting skilled and knowledgeable actors in the decision process? Intensely discussed though they were, the mandates can hardly be said to have become the object of a well-defined field of expertise, complete with unified methods, systematized bodies of knowledge and formalized procedures of certification for its experts. Institutional expert discourses on the mandates, diverse and lacking cohesion as they were, were often smokescreen for colonial rule as usual. Yet the times were changing, and because international organizations relied on the formalization (through comparison and quantification) and publicity of information, it opened a space where would‑be experts coming from different corners could present alternative views on colonial rule.